New Dynamics in Indian Ocean: A study of Pakistan, China and India under Regional Security Complex - Khizar, Sundas (Journal of Nautical Eye and Strategic Studies, 2023)
The Indian Ocean is significant for the South Asian region and the world powers. The power politics and security challenges are interlinked from an international perspective. India holds an important position due to its vast coastal line. The major challenge for India in the Indian Ocean region is the growing influence of Pakistan and China under the CPEC and the BRI flag. Relations between India and Pakistan have historically been tense, and the future does not appear to promise improvement. At the same time, China is India’s largest trading partner and shares a long border. The paper will analyze the growing scenario and effects in light of the Regional Security Complex approach by Barry Buzan and Ole Weaver. The security challenges in the Indian Ocean are not confined to the three states (China, Pakistan and India) but continuously evolving with the involvement of power politics of the regional and international players. The paper will explain three leading states' actions in the Indian Ocean region and perceptions through the RSC model. According to RSC, threats travel from state to state and region to region. The group of states in a region have a main concern about their national security linked with each other such that they cannot be handled separately. Here, the question arises of how regional ties address the conventional dangers and provide the framework for assessing the response by the three major powers concerning their interest in the Indian Ocean.